Literature as a Medium for Value Internalization: Exploring Islamic Education within the Realm of 3 Color - Muhammad Maghfi Fedrya; Sa’idy; Beti Susilawati; Nadia Eka Sauwitri; Shriya Sinha (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2026)
This study examines the integration of Islamic values in the novel Ranah 3 Warna by Ahmad Fuadi and explores its relevance as a learning media for Islamic Religious Education (IRE) at MAN 1 Bandar Lampung. Using a mixed-methods approach, this research investigates how the novel conveys Islamic values through character development, conflicts, and the moral dilemmas faced by the protagonist, as well as how these values can be applied in an educational context. The findings show that the novel is effective in conveying values such as faith, discipline, responsibility, hard work, patience, and social benefits through its narrative and character development. These values, presented in real-life contexts, provide a reflective learning experience for students, making them easier to understand and internalize. Additionally, the study reveals that this novel can serve as a valuable pedagogical tool in IRE learning, encouraging reflective discussions, character-building activities, and student motivation. The relevance of the novel in IRE teaching lies in its ability to bridge the gap between abstract Islamic concepts and students' real-life experiences, helping them understand the why and how of applying Islamic values. This study contributes to the field of Islamic Education by advocating the use of literature as a dynamic medium to strengthen moral and character education in schools.